(untitled) (Revista de Ciências Agroveterinárias, 2019)
In this study, four formulations of Italian-type salami were prepared, being one antioxidant free (control), one containing synthetic antioxidant (BHT) and two containing propolis extract (0.01% and 0.05%). The samples were submitted to microbiological and sensorial analyses and texture and color profiles, besides the weight loss and the pH during the maturation period. The results showed weight loss of the formulations during maturation, indicating that the incorporation of propolis did not affect the drying process. The formulation with 0.01% propolis showed a more intense red color at the end of maturation compared with the others. The pH values varied between some samples as well as in relation to the maturation day. The addition of BHT accelerated the dehydration process of salami at the end of the maturation period, making it harder. The control formulations and that with 0.05% propolis added showed better results for the texture profile, although they did not differ from the others in relation to the texture during the sensorial test. The control formulation and that containing BHT showed the best results for purchase intent and preference. Moreover, all formulations presented certainty percentage of purchase above 70%, suggesting acceptance by consumers.